Smart Drug Delivery System 2016
DOI: 10.5772/61932
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots - From Emergence to Nanotheranostic Applications

Abstract: Quantum dots are at the cutting edge of nanotechnology development. Due to their unique optical and physical properties, they have potential applications in many avenues of medicine and biotechnology. With the advancements in nano-sciences, novel applications of quantum dots are constantly being explored for drug delivery and bioimaging. Graphene quantum dots (GQDs) are nanoparticles of graphene with properties of quantum dots as well as graphene. GQDs have ignited remarkable research interest in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 105 publications
0
12
0
2
Order By: Relevance
“…Studies have shown that quantum dots can be successfully used for imaging because they exhibit a high bioimaging potential (Wu et al, 2013, Joshi et al, 2016). In our study, the transfer of GQDs into the cell cytoplasm was also demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that quantum dots can be successfully used for imaging because they exhibit a high bioimaging potential (Wu et al, 2013, Joshi et al, 2016). In our study, the transfer of GQDs into the cell cytoplasm was also demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Even if several in vitro and in vivo studies have demonstrated the physiological ability of functional graphene nanomaterials to promote interfacial biointeractions with mammalian cells as well as their potential toxicity in different tissues and organs, the toxicity risks of graphene-based materials are strongly dependent on their surface functionalization and size [ 16 ]. The next generation members of graphene-family, the graphene quantum dots (GQD), have shown even more promising applications in cancer treatments, pulse sensing, and prosthetics [ 17 , 18 , 19 ]. When compared with other carbon-based nanomaterials and to conventional quantum dots (QD), GQD originating from graphene or various organic sources have some particularly unusual chemical/physical properties, such as low toxicity, chemical inertness, water solubility, and biocompatibility, which make them ideal nanocarriers for drug delivery [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, great attention is focused on soluble graphitic structures belonging to the new family of carbon‐based nanodots with diameters smaller than 30 nm . Amongst them, graphene quantum dots (GQDs) , well‐known for their low‐cost synthesizing strategies, biocompatibility, excellent water solubility, and photophysical features, are an attractive alternative of the water‐insoluble graphene in a wide variety of applications mainly in bioimaging, drug delivery and analytical sensing . Of special interest is their use as sensing and sorbent materials of a great variety of pollutants .…”
Section: Introductionmentioning
confidence: 99%